Are CB2 Receptors a New Target for Schizophrenia Treatment? - Cortez, Isadora L.; Rodrigues da Silva, Naielly; Guimarães, Francisco S.; Gomes, Felipe V. (Frontiers in Psychiatry, 2020)
Schizophrenia is a complex disorder that involves several neurotransmitters such as dopamine, glutamate, and GABA. More recently, the endocannabinoid system has also been associated with this disorder. Although initially described as present mostly in the periphery, cannabinoid type-2 (CB2) receptors are now proposed to play a role in several brain processes related to schizophrenia, such as modulation of dopaminergic neurotransmission, microglial activation, and neuroplastic changes induced by stress. Here, we reviewed studies describing the involvement of the CB2 receptor in these processes and their association with the pathophysiology of schizophrenia. Taken together, these pieces of evidence indicate that CB2 receptor may emerge as a new target for the development of antipsychotic drugs.